Customer satisfaction: Experiences in healthcare sector - Ahmad, Hartini; Allan, Mahmoud (UUM Press, 2014)
This book is written to guide readers on every aspect of customer satisfaction based on a contextualised approach and to assist in improving the service quality.It is intended as a reference in measuring customer satisfaction in a more holistic way, not only in healthcare sector but also in banking, tourism and hospitality sectors. This book provides readers with a guide on how to develop an instrument to measure customer satisfaction in different service sectors. Readers will understand how important customer-oriented is to increase customer satisfaction which subsequently helps to minimise the operation costs for organisation to sustain. This book is also suitable as a reference to private hospitals’ policy makers, managers, decision makers and strategic planners on how best to utilise the proposed model in enhancing their customer satisfaction and loyalty.